Blue moon eaudiobook - Rice, Luanne (Recorded Books Inc., 2003)
Luanne Rice, the New York Times best-selling author of Firefly Beach (L1033), masterfully conveys the emotionally complex bonds that tie families together. In Blue Moon, restauranteur Cass and her fisherman husband Billy have a passionate marriage, filled with steamy sex. But the strain of raising a hearing-impaired daughter is wearing their love thin. When disaster at sea strikes, Cass must lean on her family for the support she needs.